Radiation monitoring of agricultural soils of the Volyn region in Ukraine - Oksana Hromyk; Leonid Ilyin; Igor Grygus; Serhii Korotun; Olga Ilyina; Walery Zukow (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. The development of effective environmental management programs requires an appropriate assessment of the current state of the environment and contributes to anticipating future changes in the state of the environment. Obtaining such information is one of the main objectives of monitoring the environment, which is subject to anthropogenic stress, including radiological contamination. The distribution of radionuclides and their ability to migrate in ecological chains and concentration in individual parts requires special control in contaminated areas. Objective. The purpose of the study was to analyze the content of radionuclides ( 137Cs and 90Sr) in soils near the settlements of the zone of radioactive contamination of the Volyn region and their spatial differentiation. Priority is given to agricultural lands, soils, crop products, which necessitates the organization of targeted monitoring of the agro industrial complex. Material and methods. Radioactivity from 137Cs and 90Sr in the soil originating in the Volyn region was studied from 1996 to 2018. Radiation control was carried out on the area of 59852 ha (arable land - 38897 ha, meadows and pastures - 20955 ha). Results. A significant part of the study area has elevated levels of radioactive contamination. The density of radionuclide contamination of agricultural soils in the settlements of the region has been determined. Density of pollution of all surveyed agricultural lands 137Cs ranges from 0.01 to 2.826 Ci/km2, and 90Sr from 0.01 to 0.048 Ci/km2. Conclusions. The radiological situation in the Volyn region (Ukraine) remains stable. There are slight fluctuations of 137Cs and 90Sr, which is due to changes in weather conditions, which leads to an increase or decrease in groundwater and as a consequence - the migration of radionuclides. The most polluted were the soils of administrative districts of Manevychi and Liubeshiv.